A novel collagen glycopeptide, Pro-Hyp-CONH-GlcN, stimulates cell proliferation and hyaluronan production in cultured human dermal fibroblasts. (June 2018) - Feng, Mengmeng; Betti, Mirko
Graphical abstract: Highlights: Collagen-derived glycopeptide Pro-Hyp-CONH-GlcN stimulated skin fibroblasts' growth. The glycopeptide improved the hyaluronan biosynthesis by skin fibroblasts. The glycopeptide arrested more fibroblasts that are active in DNA synthesis phase. The glycopeptide up-regulated the expression of hyaluronan synthase-2 and -3 gene. Abstract: Pro-Hyp-CONH-GlcN (POGlcN) is a glycopeptide synthesized from a typical bioavailable collagen peptide Pro-Hyp by conjugation with glucosamine. This study investigated the effects of POGlcN on dermal fibroblast growth, hyaluronan production, and the underlying mechanism. The results suggest that the plasma digestion-resistant POGlcN stimulated the proliferation of cultured human dermal fibroblasts in a time- and concentration-dependent manner with optimal performance at 200 nmol/mL and 6 days. Comparable to Pro-Hyp, POGlcN increased the cell number to 1.5-fold and HA production to 1.4-fold of control. Edu labeling-assisted cell cycle analysis revealed that POGlcN modulated the cell cycle of fibroblasts by arresting more cells in DNA synthesis phase. Moreover, POGlcN up-regulated both hyaluronan synthase-2 and -3 gene transcriptions to 1.8-fold and 2.0-fold of control, respectively. The results implied the potency of POGlcN for improving skin health and skin regeneration.